The Loci of Stroop Interference and Facilitation Effects With Manual and Vocal Responses - Augustinova, Maria; Parris, Benjamin A.; Ferrand, Ludovic (Frontiers in Psychology, 2019)
Several accounts of the Stroop task assume that the Stroop interference effect has several distinct loci (as opposed to a single response locus). The present study was designed to explore whether this is the case with both manual and vocal responses. To this end, we used an extended form of the Stroop paradigm (Augustinova et al., 2018b) that successfully distinguishes between the contribution of the task vs. semantic vs. response conflict to overall Stroop interference. In line with past findings, the results of Experiment 1 yielded an important response modality effect: the magnitude of Stroop interference was substantially larger when vocal responses were used (as opposed to key presses). Moreover, the present findings show that the response modality effect is specifically due to the fact that Stroop interference observed with vocal responses results from the significant contribution of task, semantic, and response conflicts, whereas only semantic and response conflicts clearly significantly contribute to Stroop interference observed with manual responses (no significant task conflict was observed). This exact pattern was replicated in Experiment 2. Also, and importantly, Experiment 2 also investigated whether and how the response modality effect affects Stroop facilitation. The results showed that the magnitude of Stroop facilitation was also larger when vocal as opposed to manual responses were used. This was due to the fact that semantic and response facilitation contributed to the overall Stroop facilitation observed with vocal responses, but surprisingly, only semantic facilitation contributed with manual responses (no response facilitation was observed). We discuss these results in terms of quantitative rather than qualitative differences in processing between vocal and manual Stroop tasks, within the framework of an integrative multistage account of Stroop interference (Augustinova et al., 2018b).